Simultaneous synthesis of treatment effects and mapping to a common scale: an alternative to standardisation. (23rd January 2015) - Ades, A. E.; Lu, Guobing; Dias, Sofia; Mayo‐Wilson, Evan; Kounali, Daphne
<x xml:space="preserve">Abstract</x> Objective Trials often may report several similar outcomes measured on different test instruments. We explored a method for synthesising treatment effect information both within and between trials and for reporting treatment effects on a common scale as an alternative to standardisation Study design We applied a procedure that simultaneously estimates a pooled treatment effect and the "mapping" ratios between the treatment effects on test instruments in a connected network. Standardised and non‐standardised treatment effects were compared. The methods were illustrated in a dataset of 22 trials of selective serotonin reuptake inhibitors against placebo for social anxiety disorder, each reporting treatment effects on between one and six of a total nine test instruments. Results Ratios of treatment effects on different test instruments varied from trial to trial, with a coefficient of variation of 18% (95% credible interval 11–29%). Standardised effect models fitted the data less well, and standardised treatment effects were estimated with less relative precision than non‐standardised effects and with greater relative heterogeneity. Conclusion Simultaneous synthesis of treatment effects and mapping to a common scale make fewer assumptions than standardising by dividing effects by the sample standard deviation, allow results to be reported on a common scale, and deliver estimates with superior relative precision. © 2015 The Authors. Research Synthesis Methods published by John Wiley & Sons, Ltd.